Setting up ArcSWAT hydrological model for the Verlorenvlei catchment - Lewarne, Mireille (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2009.